Per amor del cielo Farsi cristiani a Firenze tra Seicento e Settecento - Marconcini, Samuela (Premio Istituto Sangalli per la storia religiosa, 2016)
This work outlines the phenomenon of conversions to Catholicism which took place in Florence between the 17th and 18th century, and starts by reconstructing the history of the House of Catechumens. In the second half of the 17th century, thanks to a noblewoman from Florence's bequest, the Institute offered hospitality to "infidels" of all origins, and the number of conversions increased considerably. Such liberality ended up causing a serious economic crisis, which the Lorraine Grand Dukes tried to solve in the 18th century by restricting the field of action to Tuscan subjects only. However, there was no lack of abuse and interference by clergymen, especially towards Jews.